High Frequency Mutations in pfdhfr and pfdhps of Plasmodium falciparum in Response to Sulfadoxine-Pyrimethamine: A Cross-Sectional Survey in Returning Chinese Migrants From Africa - Yan, He; Feng, Jun; Yin, Jian-hai; Huang, Fang; Kong, Xiang-li; Lin, Kang-ming; Zhang, Tao; Feng, Xin-yu; Zhou, Shui-sen; Cao, Jian-ping; Xia, Zhi-gui (Frontiers in Cellular and Infection Microbiology, 2021)
Background: Sulfadoxine–pyrimethamine (SP) is recommended for intermittent preventive treatment in Africa. However, increasing SP resistance (SPR) affects the therapeutic efficacy of the SP, and pfdhfr (encoding dihydrofolate reductase) and pfdhps (encoding dihydropteroate synthase) genes are widely used as molecular markers for SPR surveillance. Here, we analyzed single nucleotide polymorphisms (SNPs) of pfdhfr and pfdhps genes in the returned migrant workers imported from Africa to China. Methods: In total, 159 blood samples were collected from Plasmodium falciparum-infected workers who had returned from Africa to Anhui, Shangdong and Guangxi provinces from 2017 to 2019. The SNPs of the pfdhfr and pfdhps were analyzed by nested PCR and Sanger sequencing. The genotypes and linkage disequilibrium (LD) tests were analysed by Haploview. Results: High frequencies were observed in N51I, C59R and S108N mutant alleles, with the mutation as 97.60%, 87.43% and 97.01% in pfdhfr, respectively. The prevalence of the pfdhps A437G (90.51%) was the most predominant allele, following by S436A (20.25%). A triple mutation (IRNI) in pfdhfr was the most prevalent haplotype (86.83%), and a single mutant haplotype (SGKAA; 62.66%) was predominant in pfdhps. In total, 5 haplotypes of pfdhfr gene and 13 haplotypes of pfdhps gene were identified. A total of 130 isolates with 12 unique haplotypes were found in the pfdhfr-pfdhps combined haplotypes, most of them (n = 85, 65.38%) carried quadruple allele combinations (CIRNI-SGKAA). Conclusion: A high prevalence of point mutations in the pfdhfr and pfdhps genes to P. falciparum isolates among migrant workers from Africa. Therefore, continuous molecular monitoring, in-vivo monitoring of ACT efficacy and additional control efforts among migrant workers are urgently needed.